Experimental study on thermal plume characteristics of building façades based on PIV technology. (February 2022) - Han, Dongliang; Zhang, Tiantian; Qin, Yuxin; Tan, Yufei
Highlights: Establish a static wind test platform based on reduced-scale building model and PIV technology. Test and compare building model thermal plumes under different surface heat fluxes. Acquire temperature and velocity test data of typical thermal plumes. Abstract: The dense distribution of high-rise buildings greatly reduces the ventilation capacity of the modern cities, leading to frequent occurrence of windless weather and accelerated accumulation of heat and pollutants in urban regions. Under no-wind conditions, the thermal plume generated from buoyancy effect of building façades tends to be the only way for heat and pollution discharging for urban environment. In order to study the plume characteristics of building façades under no-wind conditions, this study establishes a static wind test platform based on reduced-scale building model and particle image velocimetry (PIV). Using the platform, the thermal plumes under different surface heat fluxes were tested and compared. The results show that in the vertical direction, with the increase of the height from the ground, the wind speed keeps increasing, but the temperature remains almost unchanged. In the horizontal direction, with the increase of the distance from model surface, the air velocity first increases and then decreases, the temperature first drops sharply and then remains unchanged. At y/D = 0.1, the air velocity reaches the maximum, and the temperature reaches the minimum at about y/D = 0.8. The increment of the surface heat flux slightly increases the air temperature and air velocity in a small range near the wall. Generally, through the PIV test, the scope of the impaction of building facades' thermal plume is limited within half the thickness of the building.